MARKETING MANAGEMENT OF ISLAMIC EDUCATIONAL INSTITUTIONS IN ACCEPTING NEW STUDENTS AT THE SA'ADATUDDARAIN ISLAMIC BOARDING SCHOOL, TAHTUL YAMAN VILLAGE, JAMBI CITY - M. Subhan (Jurnal Manajemen Pendidikan, 2026)
This study was motivated by the increasing competition among Islamic educational institutions in attracting new students, thus requiring a focused marketing management strategy that remains based on Islamic values. The Sa'adatuddarain Islamic Boarding School, Tahtul Yaman Village, Jambi City, faces challenges in managing its new student admission system in order to remain attractive to the community. This study aims to analyze the marketing management strategies implemented, identify supporting and inhibiting factors, and examine their implementation based on the 7P marketing mix concept. This study uses a qualitative approach with a descriptive method. The research subjects consisted of the Head of Administration and teachers at the boarding school. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used the Miles and Huberman interactive model, which included data reduction, data presentation, and conclusion drawing, with validity testing through triangulation. The results of the study indicate that marketing strategies are carried out through the strengthening of flagship programs, promotion based on direct communication and social media, improving the quality of human resources, and strengthening the image of the institution based on Islamic values. The elements of product, promotion, human resources, and process are the dominant aspects in attracting new students.